MATERI MUATAN MENAMPUNG KONDISI KHUSUS DAERAH DALAM PASAL 14 UNDANG-UNDANG NOMOR 12 TAHUN 2011 TENTANG PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Azas, Ismail; Hufron, Hufron; Setyadji, Sri (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The authority for the formation of Regional Regulations is regulated in Article 18 paragraph (6) of the 1945 Constitution of the Republic of Indonesia. The phrase content material accommodates the special conditions of regions for one of the material charges in Regional Regulations regulated in Article 14 of Law Number 12 of 2011 concerning Formation of Regulations Legislation. The philosophy of Article 18A paragraph (1) of the 1945 Constitution of the Republic of Indonesia, the phrase regional specificity and diversity. Legal issues in this normative legal research: What is meant by the phrase material content accommodating the special conditions of the region in the Perda as referred to in Article 14 of Law Number 12 of 2011? Does the urgency of the charge material accommodate the special conditions of the area? The content material phrase in the article by article explanation of Law Number 12 of 2011 is declared